Vaginal Delivery at Term in a Woman with a Spontaneous Heterotopic Pregnancy Treated with Laparoscopic Salpingectomy - Michail Diakosavvas; Nikolaos Blontzos; Georgios Daskalakis; Athanasios Protopapas; Nikolaos Kathopoulis; Panagiotis Antsaklis; Grigorios Derdelis; Kyveli Angelou; Zacharias Fasoulakis; Dimitrios Loutradis; Marianna Theodora (Hindawi Limited, 2020)
Background. The coexistence of an intrauterine pregnancy and an ectopic pregnancy (heterotopic pregnancy) is an extremely rare, yet major, complication during pregnancy. The early diagnosis of a heterotopic pregnancy is of great importance for fetal viability, maternal safety, and the progression of an uncomplicated intrauterine pregnancy. Case Presentation. We report a case of a naturally conceived heterotopic tubal pregnancy in a 37-year-old primigravida. The patient presented with continuous, dull, lower abdominal pain and a positive urine pregnancy test which was conducted a week prior to the start of the pain. The patient was hospitalized, and based on the clinical image and after strict monitoring, she was diagnosed with a heterotopic pregnancy. She was treated with laparoscopic salpingectomy after the rupture of the ectopic pregnancy while the desired intrauterine gestation continued without any complications. The pregnancy resulted in the birth of a healthy infant through vaginal delivery. Discussion. Strict monitoring with multiple sonographic evaluations should always be conducted in women with abnormal serum beta-hCG, adnexal abnormalities, or clinical symptoms, while heterotopic pregnancy should be in differential diagnosis and treatment should not be delayed since emerge management is important for the progression of the intrauterine pregnancy.